Gagnon, ed. Historical Literacy - The Case of History in American Education - Madaras, Larry (Teaching History: A Journal of Methods, 1991)
In 1987 seventeen “outstanding” scholars and teachers formed the Bradley Commission on History in Schools to “explore the conditions that contribute to or impede, the effective teaching of history in American schools”. In addition, they formed the commission "to make recommendations on the curricular role of history,” and to "improve the teaching of history as the core of social studies in the schools.” Historical Literacy: The Case for History in American Education contains the complete report of the commission and seventeen essays by leading historians and teachers about the major issues surrounding the teaching of history. The essays center around five themes: “Curriculum Reform,” “The Changing Role of History in Schools,” “History and Liberal Education,” “Old and New Patterns of History,” and “Towards Better History in Schools.”